2018
DOI: 10.1007/s00417-018-4046-1
|View full text |Cite
|
Sign up to set email alerts
|

Inverted internal limiting membrane insertion versus standard internal limiting membrane peeling for macular hole retinal detachment in high myopia: one-year study

Abstract: Compared to conventional ILM peeling, inverted ILM insertion has a higher MH closure rate and tendency of better postoperative VA in patients with MHRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…We have also shown that EZ restoration was better in the inverted ILM flap group than that of ILM peeling group. Our result is similar to that of another study where the inverted ILM flap technique resulted in a significantly better postoperative BCVA than did the ILM peeling technique [30].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We have also shown that EZ restoration was better in the inverted ILM flap group than that of ILM peeling group. Our result is similar to that of another study where the inverted ILM flap technique resulted in a significantly better postoperative BCVA than did the ILM peeling technique [30].…”
Section: Discussionsupporting
confidence: 90%
“…e full text of the remaining 13 studies was evaluated; two studies had unqualified data, two did not meet the inclusion criteria, one was contextually irrelevant, and one contained data that could not be extracted. Eventually, seven studies [19,20,[26][27][28][29][30] with a total of 198 eyes (84 in the inverted ILM flap group and 114 in the ILM peeling group) were included in our meta-analysis. e characteristics of the seven studies are depicted in Table 1, and the results of their quality assessment are reported in Supplementary Table 1.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In highly myopic eyes, a macular hole with retinal detachment (MHRD) can occur. Vitrectomy with removal of cortical vitreous and ILM and gas or silicone oil tamponade has become the standard of care for MHRD treatment [94]. Although anatomic reattachment can be achieved, the success rate of MH closure ranges from 50% to 70% and poor postoperatively visual acuity was reported [23, 95, 96].…”
Section: Surgical Techniquesmentioning
confidence: 99%